A Novel Mutation c.841C>T in COPA Syndrome of an 11-Year-Old Boy: A Case Report and Short Literature Review - Zeng, Jingxia; Hao, Jing; Zhou, Wei; Zhou, Zhaoqun; Miao, Hongjun (Frontiers in Pediatrics, 2021)
COPA syndrome, a rare autosomal dominant disorder manifested by abnormal intracellular vesicle trafficking, is caused by auto-immune and auto-inflammatory abnormalities. COPα, an α subunit of the coatomer protein complex I (COPI), helps to retrograde the transport of vesicles from Golgi to endoplasmic reticulum (ER). The COPα gene mutations can affect the expression of COPα protein in the cell. Here we reported the first COPA case of an 11-year-old boy with c.841C>T, p.R281W mutation. Our conservative analysis indicated that arginine at position 281 was located in a highly evolutionary-conservative region. Immunosuppression and corticosteroids therapy might not improve the long-term outcome of COPA patients. For patients with pulmonary disease, polyarthritis, and/or kidney disorder, and suspected of COPA, genetic analysis should be conducted promptly for early diagnosis.